In Vivo Monitoring of Pancreatic β-Cells in a Transgenic Mouse Model - Steven J. Smith; Hongbing Zhang; Anne O. Clermont; Alvin C. Powers; Dixon B. Kaufman; Anthony F. Purchio; David B. West (Molecular Imaging)
We generated a transgenic mouse model ( RIP-luc ) for the in vivo monitoring of pancreatic islet mass and function in response to metabolic disease. Using the rat insulin promoter fused to firefly luciferase, and noninvasive technology to detect luciferase activity, we tracked changes in reporter signal during metabolic disease states and correlated the changes in luciferase signal with metabolic status of the mouse. Transgene expression was found to be specific to the pancreatic islets in this transgenic model. Basal transgene expression was tracked in male and female mice fed either a chow or a high-fat diet and in response to treatment with streptozotocin. Pancreatic bioluminescent signal increased in mice fed a high-fat diet compared with chow-fed animals. In a model of chemically induced diabetes, the bioluminescent signal decreased in accordance with the onset of diabetes and reduction of islet β-cell number. Preliminary studies using islets transplanted from this transgenic model suggest that in vivo image analysis can also be used to monitor transplanted islet viability and survival in the host. This transgenic model is a useful tool for in vivo studies of pancreatic β-cells and as a donor for islet transplantation studies.